Kajian Kesuburan Tanah di Desa Sihiong, Sinar Sabungan dan Lumban Lobu Kecamatan Bonatua Lunasi Kabupaten Toba Samosir - Rino P. C. Purba; Bintang Sitorus; Mariani Sembiring (Universitas Sumatera Utara, 2014)
This study aims to examine the fertility of the soil in the Sihiong Village, Sinar Sabungan Villageand Lumban Lobu Village, Bonatua Lunasi Subdistricts, Toba Samosir District. This research wasconducted in Sihiong Village, Sinar Sabungan Village and Lumban Lobu Village, SubdistrictsBonatua Lunasi, District Toba Samosir and Laboratory analysis of samples carried out in Researchand Technology, Faculty of Agriculture, University of North Sumatra. The method used in thisstudy is a survey method to make observations on the soil profile and on each layer of the soilhorizon to compare the soil fertility.The soil in the village Sihiong have a somewhat acidic soil pH,organic matter content is moderate, moderate cation exchange capacity capability, very low basesaturation while high levels of total soil ferrum. The soil in the Village Sinar Sabungan have acidicsoil pH, organic matter content is moderate, the ability of the cation exchange capacity of themedium, which is very low base saturation while high levels of total soil ferrum. The soil fertility inthe village of Lumban Lobu have acidic soil pH, organic matter content is moderate, the ability ofthe cation exchange capacity of the medium, which is very low base saturation while high levels oftotal soil ferrum.Keyword: Sihiong village soil profile, Sinar Sabungan village soil profile, Lumban Lobu villagesoil profile